Energy efficiency in electric motor systems : technical potentials and policy approaches for developing countries - Fleiter, Tobias (UNIDO ViennaAT, 2011)
Discusses the high potential for energy efficiency improvement in motor systems in developing as well as developed countries. Notes that system optimisation approaches that consider the whole motor system's efficiency show great potential. States that market failures and barriers such as lack of capital, higher initial costs, lack of attention by plant managers and principal agent dilemmas hamper the investment in energy efficient motor systems.